Effects of Blood Flow Restriction and Exercise Intensity on Aerobic, Anaerobic, and Muscle Strength Adaptations in Physically Active Collegiate Women - Amani-Shalamzari, Sadegh; Rajabi, Saeedeh; Rajabi, Hamid; Gahreman, Daniel E.; Paton, Carl; Bayati, Mahdi; Rosemann, Thomas; Nikolaidis, Pantelis Theodoros; Knechtle, Beat (Frontiers in Physiology, 2019)
The purpose of this study was to compare the effects of different combinations of blood flow restriction (BFR) pressure and exercise intensity on aerobic, anaerobic, and muscle strength adaptations in physically active collegiate women. Thirty-two women (age, 22.8±2.9yrs; body mass index, 22.3±2.7 kg/m2) were randomly assigned into four experimental training groups: (a) increasing BFR pressure with constant exercise intensity (IP-CE), (b) constant partial BFR pressure with increasing exercise intensity (CPP-IE), (c) constant complete BFR pressure with increasing exercise intensity (CPC-IE), and (d) increasing BFR pressure with increasing exercise intensity (IP-IE). Participants completed 12 training sessions comprised of repeated bouts of two minutes running on a treadmill with BFR interspersed by one-minute recovery without BFR. Participants completed a series of tests to assess muscle strength, aerobic and anaerobic performances. Muscle strength, anaerobic power and aerobic parameters including VO2max, time to fatigue, vVO2max and running economy improved in all groups (p ≤ 0.01). The CPC-IE group outscored the other groups in muscle strength, running economy, and time to fatigue (p < 0.05). In summary, participants with complete occlusion experienced the greatest improvements in muscle strength, aerobic and anaerobic parameters possibly due to increased oxygen deficiency and higher metabolic stress.